2020
DOI: 10.5194/isprs-archives-xliii-b2-2020-119-2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flight Altitude on Unmanned Aerial Photogrammetric Survey of the Snow Height on Mount Lebanon

Abstract: Abstract. In Lebanon, the seasonal snowpack is poorly monitored despite its importance for water resource supply. The snow accumulates on Mount Lebanon in karstic depressions named “sinkholes.” It is important to monitor the evolution of the snow height inside those “sinkholes”, because of their key role as “containers” for seasonal snow. UAV photogrammetry is a major technological breakthrough which allows an accurate monitoring of the snow height. Because the impact of flight parameters on snow height retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
2
3
0
Order By: Relevance
“…They were differentiated in terms of AGL height (30, 40, 50, 60, 70, 80 m), overlap between photographs (40/70%, 50/80%) and the use or absence of GCPs. It was shown that decreasing the flight height has a positive effect on the detail of the obtained products which was also confirmed in the study [100] and increases the accuracy of the RMSE readings. For comparison, the value of the RMSE error when using an altitude of 30 m was 3.8 cm at 80/50% coverage and 5.4 cm at 70/40% coverage, while when using an altitude of 80 m it was 9.5 cm at 80/50% coverage and 10.0 cm at 70/40% coverage.…”
Section: Photograph Blocks Flight Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…They were differentiated in terms of AGL height (30, 40, 50, 60, 70, 80 m), overlap between photographs (40/70%, 50/80%) and the use or absence of GCPs. It was shown that decreasing the flight height has a positive effect on the detail of the obtained products which was also confirmed in the study [100] and increases the accuracy of the RMSE readings. For comparison, the value of the RMSE error when using an altitude of 30 m was 3.8 cm at 80/50% coverage and 5.4 cm at 70/40% coverage, while when using an altitude of 80 m it was 9.5 cm at 80/50% coverage and 10.0 cm at 70/40% coverage.…”
Section: Photograph Blocks Flight Methodssupporting
confidence: 78%
“…Similar conclusions were reached in another study [101]. DEMs generated from images acquired at five different flight heights (50,100,150,200, 250 m AGL) were analysed. The georeferencing was performed using 18 GCPs while the accuracy assessment was based on 385 CPs.…”
Section: Photograph Blocks Flight Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…However, when the flight velocity was 11 m/s, the velocity-driven variation in the point density was the greater: 5 pt/m 2 at 70 m high and 10–12 pt/m 2 at 30–50 m high. Conclusively, it is preferable to fly the UAV at the slower velocity and the lower height, but note that this will reduce the coverage area and increase the flight operation time [ [67] , [68] , [69] , [70] ].…”
Section: Results From Test Flight Sitementioning
confidence: 99%
“…Especially during emergence, it is important to determine these parameters to precisely determine the sprout rate and their traits. It has been shown that increased flight altitude results in decreased resolution of the densified surface model (DSM) which is used to extract height and related parameters ( Abou Chakra et al., 2020 ). While increasing the UAV flight height reduces the time taken to take mages in the same field, the lesser number of images captured reduces the processing time.…”
Section: Introductionmentioning
confidence: 99%